2010
DOI: 10.1175/2009jas2965.1
|View full text |Cite
|
Sign up to set email alerts
|

Simulated Electrification of a Small Thunderstorm with Two-Moment Bulk Microphysics

Abstract: Electrification and lightning are simulated for a small continental multicell storm. The results are consistent with observations and thus provide additional understanding of the charging processes and evolution of this storm. The first six observed lightning flashes, all negative cloud-to-ground (CG) flashes, indicated at least an inverted dipole charge structure (negative charge above positive). Negative CG flashes should be energetically favorable only when the negative charge region contains appreciably mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
312
1
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 409 publications
(359 citation statements)
references
References 64 publications
11
312
1
2
Order By: Relevance
“…On the other side, the two-moment NSSL scheme predicts average graupel particle density, allowing this to span the range from frozen drops to low-density graupel (Mansell et al 2010). Given the specific geographical setting of the western Mediterranean Basin, we also sample the CCN uncertainty as the variability of aerosol concentration-depending on the origin of the air mass affecting the area-is clearly influential and not considered by standard tabulated aerosol parameters.…”
Section: B Mps Experimentsmentioning
confidence: 99%
“…On the other side, the two-moment NSSL scheme predicts average graupel particle density, allowing this to span the range from frozen drops to low-density graupel (Mansell et al 2010). Given the specific geographical setting of the western Mediterranean Basin, we also sample the CCN uncertainty as the variability of aerosol concentration-depending on the origin of the air mass affecting the area-is clearly influential and not considered by standard tabulated aerosol parameters.…”
Section: B Mps Experimentsmentioning
confidence: 99%
“…Additionally, the existence and nature of the lower positive charge center has a significant influence on the occurrence of CG flashes (Jacobson and Krider 1976). When there is a large positive charge center at low altitude above ground level, this can also inhibit the production of negative CG flashes (Nag and Rakov 2009;Mansell et al 2010). Storms that exhibit inverted and/or complex charge structures frequently have high IC flash rates, discourage the production of negative CG flashes, and encourage the production of positive CG flashes within the convective region of the storm Rutledge 1998, 2003;Wiens et al 2005;Carey and Buffalo 2007;Qie et al 2009;Bruning et al 2014;Fuchs et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Sections 7.20 and 7.21 in MacGorman and Rust (1998) provide additional details. Helpful modeling work on this topic is presented in Mansell et al (2010).…”
Section: Introductionmentioning
confidence: 99%
“…One of those four options is option zero (mp_physics=0), which means that no microphysics is used. Another one is the NSSL 2-moment 4-ice scheme (Mansell et al, 2010) with predicted CCN (mp_physics=18), which is suggested for use with idealized cases rather than real ones. The remaining two are spectral bin microphysics, i.e., fast (Khain et al, 2010), and full (Khain et al, 2004) versions of HUJI (Hebrew University of Jerusalem, Israel), i.e., 20 mp_physics=30 and mp_physics=32, respectively, which are beyond the scope of this study.…”
Section: Mp Schemesmentioning
confidence: 99%
“…Reisner et al (1998;RRB98) type-MP5: Ferrier (New Eta) Scheme (NOAA, 2001), MP7: Goddard Scheme (Tao et al, 1989), MP8: Thompson Scheme (Thompson et al, 2008), and MP28: AerosolAware Thompson Scheme (Gilmore et al, 2014); 5 4. Ziegler (1985) type-MP17: NSSL 2-moment Scheme (Mansell et al, 2010), MP19: NSSL 1-moment 7-class Scheme, and MP21: NSSL 1-moment 6-class Scheme (Gilmore et al, 2004).…”
Section: Mp Schemesmentioning
confidence: 99%